Report of the Managing Director to the International Monetary and Financial Committee on the IMF's Policy Agenda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This report provides an update on the work and direction of the Fund since the 2006 Spring Meetings and for the period ahead. Over the past six months work has concentrated on implementing key aspects of the Medium-Term Strategy (MTS), especially in the areas of surveillance and quotas and voice. In surveillance, the new multilateral consultation has been launched, the Board is reviewing the Fund's general decision on surveillance (the 1977 Decision on Surveillance over Exchange Rate Policies), and it has discussed the possibility of setting a remit for surveillance based on a set of objectives and priorities. Progress is being made on quotas and voice and specific proposals are contained in the report and resolution from the Executive Board to the Board of Governors. Work in other areas has focused on the role of the Fund in emerging markets and low-income countries (LICs), building institutions and capacity, and managing an effective institution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet